Notes relating to the Flora of Bhutan: XXV. Boraginaceae. I. Onosma griersonii, a new species from Bhutan - Mill, R. R. (Edinburgh Journal of Botany, 2010)
The new species Onosma griersonii R. R. Mill (Boraginaceae) is described from Bhutan. The species belongs to O. sect. Maharanga (DC.) C. B. Clarke.